Life, Fish and Mangroves : Resource governance in costal Cambodia - Melissa Marschke (Les Presses de l'Université d'Ottawa | University of Ottawa Press, 2012)
In Life, Fish and Mangroves, Melissa Marschke explores the potential of resource governance, offering a case study of resource-dependent village life. Following six households and one village-based institution in coastal Cambodia over a twelve-year period, Marschke reveals the opportunities and constraints facing villagers and illustrates why local resource management practices remain delicate, even with a sustained effort. She highlights how government and business interests in community-based management and resource exploitation combine to produce a complex, highly uncertain dynamic. With this instructive study, she demonstrates that in spite of a significant effort, spanning many years and engaging many players, resource governance remains fragile and coastal livelihoods in Cambodia remain precarious.